PERAN MEDIASI KESADARAN PAJAK DALAM HUBUNGAN PEMUTIHAN PAJAK DAN KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Muhammad Wisnu Girindratama; Aulia Nur Firdaus Rahmatullah (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This study aimed to obtain empirical evidence on the mediation effects of tax awareness mediation on the relationship between tax evasion and tax compliance. This research used an online survey through Google Forms. This study's population is taxpayers in the East Java region. Respondents were selected using purposive sampling techniques. In determining whether there is an influence of mediation, the Sobel test was carried out using Jose's Medgraph Online Software. The results showed that the level of tax awareness partially mediates the relationship between tax evasion and motor vehicle taxpayer compliance.